Glucagon-Like Peptide-1 Receptor Agonists: Beta-Cell Protection or Exhaustion?. (July 2016) - van Raalte, Daniël H; Verchere, C. Bruce
Abstract : Glucagon-like peptide (GLP)-1 receptor agonists enhance insulin secretion and may improve pancreatic islet cell function. However, GLP-1 receptor (GLP-1R) agonist treatment may have more complex, and sometimes deleterious, effects on beta cells. We discuss the concepts of beta cell protection versus exhaustion for different GLP-1R agonists based on recent data.